The Relation of the Extracranial Spinal Accessory Nerve to the Sternocleidomastoid Muscle and the Internal Jugular Vein - Amuti, Thomas Mombo (Craniomaxillofac Trauma Reconstr, 2019)
The spinal accessory nerve (SAN) exhibits variant anatomy in its relation to the internal jugular vein (IJV) as well as the sternocleidomastoid muscle (SCM). These variations are important in locating the nerve during surgical neck procedures to avoid its inadvertent injury. These variations, however, are not conserved among different populations and data from the Kenyan setting are partly elucidated. This study, therefore, aims to determine the variant anatomical relationship of the SAN to the SCM and IJV in a select Kenyan population. Forty cadaveric necks were studied bilaterally during routine dissection and the data collected were analyzed using SPSS version 21. Means and modes were calculated for the point of entry of the SAN into the posterior triangle of the neck as well as for its relation to the SCM. Side variations for both of these were analyzed using Student's t -test. Data relating the SAN to the IJV were represented in percentages and side variations were analyzed using the chi-square test. The SAN point of entry into the posterior triangle of the neck was 5.38 cm (3.501–8.008 cm) on the left side and 5.637 cm (3.504–9.173 cm) on the right side ( p  = 0.785) from the mastoid process. The nerve perforated the SCM in four cases (10%) on the left side and in eight cases (20%) on the right ( p  = 0.253). The SAN lay predominantly medial to the IJV on both sides of the neck, 87.5% on the left side of the neck versus 82.5% on the right ( p  = 0.831). In conclusion, the variant relation of the SAN to the IJV and SCM as observed in this setting is an important consideration during radical neck procedures and node biopsies.